Uji Bioinsektisida Ekstrak Buah Bintaro dan Umbi Gadung Terhadap Hama Walang Sangit (Leptocorisa acuta T.) - Bahri, Syaiful; Ilim, Ilim; Qudus, Hardoko Insan; Ambarwati, Yuli; Wulandari, Ika Rizki (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2023)
Insecticides are a type of pesticide that is commonly used by farmers to eradicate insect pests, one of which is the stink bug. Excessive use results in resistance and contamination of soil, water, and air. Another alternative is bioinsecticides which are safe and do not cause resistance. In this study, the samples used were gadung and bintaro root extracts. The method used is maceration, after the maceration process, the filtrate will be tested on the target animal, looking for the best insecticide mortality and screening for phytochemicals. Lastly, the best bioinsecticide solutions were identified using FT-IR and UV-Vis spectrophotometers. The best bioinsecticide solutions with 60% and 40% mortality were bioinsecticides with a concentration of 70% gadung and 30% gadung 20% bintaro. Phytochemical screening tests were carried out on both of them, the results were positive for terpenoids and alkaloids. Identification using the FTIR spectrophotometer showed that the bioinsecticide solution contained secondary metabolites with O-H groups appearing at absorption wave number 3260 cm-1, C=O groups appearing at wave number 1637cm-1,, and C-H groups appearing at wave number 1359 cm-1. The results of the UV-Vis spectrum showed that the bioinsecticide solution had the C=C functional group as indicated by the appearance of peaks at a wavelength of 210 nm, 217 nm, and 223 nm.